The Influence of Pos Indonesia’s New Logo and Service Quality on Service Use Intention: The Mediating Role of Brand Image in the Pospreneur Webinar Community - Johni Eka Putra; Vanessa Gaffar; Lili Adi Wibowo; Toni Heryana; Agus Fathurohman Handoyo; Ihwan Sutardiyanta (CV. Sakura Digital Nusantara, 2026)
Purpose – This study examines the influence of Pos Indonesia’s new logo and service quality on the intention to use Pos Indonesia services, with brand image as an intervening variable. This topic is important because Pos Indonesia has renewed its visual identity as part of its transformation, while consumer intention in service industries is influenced not only by visual elements but also by service experience and brand perception. Design/methodology/approach – This study employed a quantitative approach with an explanatory survey design. Primary data were collected through questionnaires distributed to members of the Pospreneur Webinar Community. The research variables included the new logo, service quality, brand image, and intention to use services. The data were analyzed using Structural Equation Modeling–Partial Least Squares (SEM-PLS) to test direct and indirect relationships among variables. Finding/Results – The findings show that the new logo has a significant positive effect on brand image, but does not directly have a significant effect on intention to use services. Service quality has a significant positive effect on both brand image and intention to use services. Brand image also significantly influences intention to use services and mediates the relationship between the new logo and service quality toward intention to use services. Originality/Value – This study indicates that logo renewal can strengthen brand image, but consumer intention to use services is more strongly driven by service quality and positive brand perception. Therefore, rebranding should be supported by consistent service improvement.